Exploration of the ocular surface infection by SARS-CoV-2 and implications for corneal donation: An ex vivo study. - Corantin Maurin; Zhiguo He; Marielle Mentek; Paul Verhoeven; Sylvie Pillet; Thomas Bourlet; Françoise Rogues; Jean Loup Pugniet; Thierry Peyragrosse; Marion Barallon; Chantal Perrache; Inès Aouimeur; et al. (PLoS Medicine, 2022)
Background The risk of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) transmission through corneal graft is an ongoing debate and leads to strict restrictions in corneas procurement, leading to a major decrease in eye banking activity. The aims of this study are to specifically assess the capacity of human cornea to be infected by SARS-CoV-2 and promote its replication ex vivo, and to evaluate the real-life risk of corneal contamination by detecting SARS-CoV-2 RNA in corneas retrieved in donors diagnosed with Coronavirus Disease 2019 (COVID-19) and nonaffected donors. Methods and findings To assess the capacity of human cornea to be infected by SARS-CoV-2, the expression pattern of SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE-2) and activators TMPRSS2 and Cathepsins B and L in ocular surface tissues from nonaffected donors was explored by immunohistochemistry (n = 10 corneas, 78 ± 11 years, 40% female) and qPCR (n = 5 corneas, 80 ± 12 years, 40% female). Additionally, 5 freshly excised corneas (80 ± 12 years, 40% female) were infected ex vivo with highly concentrated SARS-CoV-2 solution (106 median tissue culture infectious dose (TCID50)/mL). Viral RNA was extracted from tissues and culture media and quantified by reverse transcription quantitative PCR (RT-qPCR) (viral RNA copies) 30 minutes (H0) and 24 hours (H24) after infection. To assess the risk of corneal contamination by SARS-CoV-2, viral RNA was tested by RT-qPCR (Ct value) in both corneas and organ culture media from 14 donors diagnosed with COVID-19 (74 ± 10 years, 29% female) and 26 healthy donors (79 ± 13 years, 57% female), and in organ culture media only from 133 consecutive nonaffected donors from 2 eye banks (73 ± 13 years, 29% female). The expression of receptor and activators was variable among samples at both protein and mRNA level. Based on immunohistochemistry findings, ACE-2 was localized mainly in the most superficial epithelial cells of peripheral cornea, limbus, and conjunctiva, whereas TMPRSS2 was mostly expressed in all layers of bulbar conjunctiva. A significant increase in total and positive strands of IP4 RNA sequence (RdRp viral gene) was observed from 30 minutes to 24 hours postinfection in central cornea (1.1 × 108 [95% CI: 6.4 × 107 to 2.4 × 108] to 3.0 × 109 [1.4 × 109 to 5.3 × 109], p = 0.0039 and 2.2 × 107 [1.4 × 107 to 3.6 × 107] to 5.1 × 107 [2.9 × 107 to 7.5 × 107], p = 0.0117, respectively) and in corneoscleral rim (4.5 × 109 [2.7 × 109 to 9.6 × 109] to 3.9 × 1010 [2.6 × 1010 to 4.4 × 1010], p = 0.0039 and 3.1 × 108 [1.2 × 108 to 5.3 × 108] to 7.8 × 108 [3.9 × 108 to 9.9 × 108], p = 0.0391, respectively). Viral RNA copies in ex vivo corneas were highly variable from one donor to another. Finally, viral RNA was detected in 3 out of 28 corneas (11%) from donors diagnosed with COVID-19. All samples from the 159 nonaffected donors were negative for SARS-CoV-2 RNA. The main limitation of this study relates to the limited sample size, due to limited access to donors diagnosed with COVID-19 and concomitant decrease in the procurement corneas from nonaffected donors. Conclusions In this study, we observed the expression of SARS-CoV-2 receptors and activators at the human ocular surface and a variable increase in viral RNA copies 24 hours after experimental infection of freshly excised human corneas. We also found viral RNA only in a very limited percentage of donors with positive nasopharyngeal PCR. The low rate of positivity in donors diagnosed with COVID-19 calls into question the utility of donor selection algorithms. Trial registration Agence de la Biomédecine, PFS-20-011 https://www.agence-biomedecine.fr/.